2019
DOI: 10.3725/jjn.49.1
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane yield loss in the ratoon crop carried over from the plant crop damaged by plant-parasitic nematode in a heavy clay field in Okinawa, Japan

Abstract: loss observed around the globe, including reductions of -% in Australia, -% in Brazil, and more than % in South Africa in plant and ratoon crops. As indicated by Blair and Stirling ( ), many of previous nematode studies in sugarcane fields were in sandy soil, in which Meloidogyne may be the most important plant-parasitic nematode species (PPN). Bull ( and ) reported a yield decline of % in plant crop and -% or more in the ratoon crop in a sandy sugarcane field infested with Pratylenchus. Bond et al. ( ) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This suggests that P. zeae population densities in roots at the early growth period of sugarcane can affect yield. The nematicide fosthiazate showed much greater reduction in the number of the root-lesion nematodes in sugarcane field soils (Kawanobe et al, 2014(Kawanobe et al, , 2016 and in sugarcane roots (Kawanobe et al, 2019) in the early growth period than later in the season. These studies (Kawanobe et al, 2016(Kawanobe et al, , 2019 showed 20% more sugarcane yield in the spring-planted crop and the ratoon crop by applying fosthiazate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that P. zeae population densities in roots at the early growth period of sugarcane can affect yield. The nematicide fosthiazate showed much greater reduction in the number of the root-lesion nematodes in sugarcane field soils (Kawanobe et al, 2014(Kawanobe et al, , 2016 and in sugarcane roots (Kawanobe et al, 2019) in the early growth period than later in the season. These studies (Kawanobe et al, 2016(Kawanobe et al, , 2019 showed 20% more sugarcane yield in the spring-planted crop and the ratoon crop by applying fosthiazate.…”
Section: Discussionmentioning
confidence: 99%
“…The nematicide fosthiazate showed much greater reduction in the number of the root-lesion nematodes in sugarcane field soils (Kawanobe et al, 2014(Kawanobe et al, , 2016 and in sugarcane roots (Kawanobe et al, 2019) in the early growth period than later in the season. These studies (Kawanobe et al, 2016(Kawanobe et al, , 2019 showed 20% more sugarcane yield in the spring-planted crop and the ratoon crop by applying fosthiazate. Fipronil may not be as effective as fosthiazate at the dose applied in this study, yet it still suppressed P. zeae in sugarcane roots and resulted in greater sugarcane yields than the non-treated control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Các nghiên cứu ở Úc, Brazil và Nam Phi cho biết năng suất mía giảm từ 10% đến 30% do tuyến trùng ký sinh thực vật gây ra và đôi khi giảm hơn 40% do tuyến trùng ký sinh thực vật ở châu Phi (Cadet & Spaull, 2005). Các nghiên cứu trước đây (Kawanobe et al, 2016(Kawanobe et al, , 2019 chỉ ra khoảng 20% thiệt hại về năng suất khi trồng vụ xuân và các vụ mùa liên tiếp do tuyến trùng ký sinh thực vật gây ra (chủ yếu là Pratylenchus) ở Okinawa, Nhật Bản. Như vậy, sự tích lũy mật số của dịch hại qua nhiều vụ trồng liên tiếp, nhất là các vùng chuyên canh có thể liên quan đến sự suy giảm năng suất mía.…”
Section: Giới Thiệuunclassified